Analisis Gaya Belajar Peserta Didik pada Era Digitalisasi di Sekolah Dasar - Fijar Saif Alqaini; Apdoludin Apdoludin; Elvima Nofrianni (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This research was conducted in response to the rapid advancement of digital technology that has significantly transformed learning processes in elementary schools, particularly in terms of students' learning styles. The study aims to analyze the learning styles of students at State Elementary School 36/II Sarana Jaya in the context of digital-based instruction. A qualitative descriptive approach was employed, utilizing data collection techniques such as in-depth interviews, classroom observations, and documentation. Data were analyzed descriptively to explore the tendencies of visual, auditory, and kinesthetic learning styles as they manifest in digital learning environments. The findings revealed that visual and auditory learning styles were predominant among students. Digital media such as instructional videos, interactive quizzes, and visual presentations helped enhance student motivation and engagement. Nevertheless, some obstacles were identified, including limited internet access, inadequate digital infrastructure, and students’ lack of digital literacy. The study concludes that aligning digital learning tools with students’ individual learning preferences can improve learning effectiveness and foster active participation. In the future, integrating technology that supports diverse learning styles is expected to create a more inclusive and engaging educational environment at the elementary level.